The Influence of Leaflet Media on Students' Attitudes Regarding Sexually Transmitted Infections - Hasnidar, Hasnidar; Mustar, Mustar; Asrina, Andi; Safitri, Nadia Nur (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
One of the main problems faced by adolescents, especially in Indonesia at this time, is the problem of reproductive health, with the number of cases as of the first quarter of 2022 as many as 10,252 cases. Sexually transmitted infections are the impact of the lack of knowledge about reproductive health for adolescents. Providing health education using leaflet media is expected to increase knowledge and shape the attitudes of adolescents related to sexually transmitted infections. This study aimed to determine the effect of using leaflet media on adolescents' attitudes at Sipatokkong Mambo University, Bone Regency. The type of research used is a quantitative method using a pre-experimental approach with one group pretest-posttest design without a control group. The data collection instrument used a questionnaire to find out how students' attitudes toward preventing sexually transmitted infections (STIs). Measurements were made before and after health education was carried out using leaflet media. The population in this study was 34 student association administrators. The sample used in this study was 34 respondents, with the sampling technique using total sampling. Data is processed with the help of computer applications. Data analysis used a paired sample t-test statistic. The results showed that the average score of students' attitudes before implementing health education using leaflets was 36.41. After implementing health education using leaflet media, the average value of student attitudes was 41.91. The results of the t-test obtained a value of p = 0.000 <0.05, so it can be concluded that the use of leaflet media as a medium for health education has a significant effect on student attitudes related to sexually transmitted infections. Therefore, it is suggested for health workers to be able to use the media leaflet in conducting health education to shape student attitudes in preventing sexually transmitted infections (STIs).